Pleasure and the good life : Plato, Aristotle, and the Neoplatonists - Riel, Gerd van. (Philosophia Antiqua, 2000)
This volume deals with the general theory of pleasure of Plato and his successors. The first part describes the two paradigms between which all theories of pleasure oscillate: Plato's definition of pleasure as the repletion of a lack, and Aristotle's view that pleasure is the perfect performance of an activity. After an excursus on Epicureans and Stoics, the book concentrates on Neoplatonism, opposing the 'standard Neoplatonic view' of Plotinus and Proclus to the original viewpoint of Damascius' commentary on Plato's Philebus . The volume sheds light on the discussion between hedonists and anti-hedonists, by concentrating on the 'crucial point' at which any philosophical analysis of the good life (hedonistic or other) ought to argue that the life of the philosopher is the most desirable, and thus truly pleasurable, life.